Dominant renin gene mutations associated with early-onset hyperuricemia, anemia, and chronic kidney failure - Zivná, Martina; Hůlková, Helena; Matignon, Marie; Hodanová, Katerina; Vylet'al, Petr; Kalbácová, Marie; Baresová, Veronika; Sikora, Jakub; Blazková, Hana; Zivný, Jan; Ivánek, Robert; Stránecký, Viktor; et al. (American journal of human genetics, 2009)
Through linkage analysis and candidate gene sequencing, we identified three unrelated families with the autosomal-dominant inheritance of early onset anemia, hypouricosuric hyperuricemia, progressive kidney failure, and mutations resulting either in the deletion (p.Leu16del) or the amino acid exchange (p.Leu16Arg) of a single leucine residue in the signal sequence of renin. Both mutations decrease signal sequence hydrophobicity and are predicted by bioinformatic analyses to damage targeting and cotranslational translocation of preprorenin into the endoplasmic reticulum (ER). Transfection and in vitro studies confirmed that both mutations affect ER translocation and processing of nascent preprorenin, resulting either in reduced (p.Leu16del) or abolished (p.Leu16Arg) prorenin and renin biosynthesis and secretion. Expression of renin and other components of the renin-angiotensin system was decreased accordingly in kidney biopsy specimens from affected individuals. Cells stably expressing the p.Leu16del protein showed activated ER stress, unfolded protein response, and reduced growth rate. It is likely that expression of the mutant proteins has a dominant toxic effect gradually reducing the viability of renin-expressing cells. This alters the intrarenal renin-angiotensin system and the juxtaglomerular apparatus functionality and leads to nephron dropout and progressive kidney failure. Our findings provide insight into the functionality of renin-angiotensin system and stress the importance of renin analysis in families and individuals with early onset hyperuricemia, anemia, and progressive kidney failure.
Keywords: mutace; dospělí; Kidney; Female; buněčné linie; věk při počátku nemoci; Anemia; genetická vazba; dítě; předškolní dítě; chronické selhání ledvin; Pedigree; Adult; počítačová simulace; ženské pohlaví; mladý dospělý; Renin; rodokmen; Adolescent; hyperurikemie; lidé; Mutation; Hyperuricemia; Kidney Failure, Chronic; Cell Line; Computer Simulation; Male; Genetic Linkage; Child, Preschool; dominantní geny; Young Adult; Sequence Analysis, DNA; lidé středního věku; Child; Age of Onset; anemie; mužské pohlaví; sekvenční analýza DNA; ledviny; Genes, Dominant; renin; Middle Aged; mladiství; Humans